Inexpensive current-voltage system with electronically-controlled resistance under xenon arc light for solar cell efficiency measurements - Mukhlis Mokhtar; Samir Ahmad; Suhaila Sepeai; Norizam M. Daud; Saleem H. Zaidi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Crystalline silicon solar cell efficiency is required in order to accurately determine its performance and evaluate the fabrication process. Extensive automation has led to development of expensive instrumentation. In this study, simple, inexpensive method for measuring solar cell efficiency is reported. A controllable direct current (dc) illumination intensity method based on low power xenon arc lamps was designed and constructed. Low resistance electrical contacts were formed with conventional front surface probes and back surface Au-plated metal plate with vacuum attachment. In order to measure current-voltage (I-V) response, variable resistance approach was chosen. Commercially available, low cost electronic loads power supply is used to precisely vary resistance while measuring cell voltage and current. The resistance is controllably varied from a short circuit to an open circuit position on the I-V curve while measuring cell voltage and current. Plotting current as a function of voltage generates the characteristic solar cell I-V response. Solar cell efficiency measurements were recorded and plotted using LabVIEW program. The light intensity was varied by increasing number of high intensity discharge (HID) 50 W from 1 to four in order to vary respective illumination intensities from 330 to 1200 W/m2 range. The variation in light intensity was aimed at investigation of the electronic loads power supply at low and high currents. This I-V tester has been applied to different types of solar cell to validate its performance. Solar cells measured as part of this study included commercial silicon solar cell and laboratory solar cells with phosphorus oxytrichloride (POCl3) and phosphoric acid (H3PO4) emitter formation. This I-V measurement system for commercial cell exhibited an efficiency of 15.83% and efficiency of 16.2% and 13.3% for solar cells with POCl3 and H3PO emitters.